Analysis of the Safety of Antihypertensive Drug Use in Elderly Patients - Ridwan (Dinasti Health and Pharmacy Science, 2024)
Hypertension is a common health condition among elderly individuals, requiring careful management through antihypertensive medications. However, the use of these medications in older adults raises concerns about the safety and prevalence of side effects, which can significantly impact their quality of life and adherence to treatment. This study aims to analyze the safety of antihypertensive medication use in elderly patients by evaluating the prevalence of common side effects, identifying potential drug interactions, and exploring factors influencing treatment success. A mixed-methods approach was used, combining quantitative data from structured surveys and clinical records with qualitative insights from semi-structured interviews with patients and healthcare providers. The results revealed that dizziness, fatigue, and hypotension were the most common side effects, with a prevalence of 25%, 18%, and 15%, respectively. Older patients and those with comorbid conditions such as diabetes were found to be more prone to these side effects. The study also identified the importance of personalized treatment approaches, with healthcare providers emphasizing regular monitoring, medication adjustments, and patient education as key strategies to mitigate risks. These findings underscore the need for tailored antihypertensive therapy in elderly patients, considering individual characteristics and potential side effects. The study highlights the critical role of healthcare providers in managing these medications safely and effectively, ensuring better outcomes for elderly patients with hypertension. Future research should focus on larger, longitudinal studies to assess long-term effects and explore alternative treatment options that minimize adverse reactions.